2022
DOI: 10.1097/inf.0000000000003713
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children in Western Countries? Decreasing Incidence as the Pandemic Progresses?: An Observational Multicenter International Cross-sectional Study

Abstract: Background: SARS-CoV-2 variations as well as immune protection after previous infections and/or vaccination may have altered the incidence of multisystemic inflammatory syndrome in children (MIS-C). We aimed to report an international time-series analysis of the incidence of MIS-C to determine if there was a shift in the regions or countries included into the study. Methods: This is a multicenter, international, cross-sectional study. We collected the MIS-C incidence from the participant regions and countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Several signs and symptoms have been reported by scientific studies or associations (Fig. 1) [6 ▪ ,12–30 ▪ ,31–33]. Fatigue is the most common symptom reported by all studies, in agreement with experiences from adult PCC clinics.…”
Section: Clinical Presentationsupporting
confidence: 83%
See 1 more Smart Citation
“…Several signs and symptoms have been reported by scientific studies or associations (Fig. 1) [6 ▪ ,12–30 ▪ ,31–33]. Fatigue is the most common symptom reported by all studies, in agreement with experiences from adult PCC clinics.…”
Section: Clinical Presentationsupporting
confidence: 83%
“…Importantly, this estimate may variate according to the SARS-CoV-2 variant causing the initial infection, or according to previous immunity (e.g. by vaccination or immunity), as happening with MIS-C, whose risk has now significantly decreased [31]. Importantly, given the methodological differences, so far it is not possible to provide data about regional or country-specific or ethnicity-specific estimates, although all controlled studies from UK, US, Switzerland suggest the 1–3% higher rates of symptoms in children with previous SARS-CoV-2 infection.…”
Section: Epidemiologymentioning
confidence: 99%
“…5 Reasons for reduced risk of negative post-acute outcomes may be related to differences in the viral spike protein or previous immunity from infection or vaccination, or both. 6 Importantly, as a non-negligible number of…”
Section: Ta B L E 1 Multivariate Logistic Regression Including Sars-c...mentioning
confidence: 99%
“…Interestingly, it has been demonstrated that children infected with Omicron also have a significantly reduced risk of developing Multisystem Inflammatory Syndrome 5 . Reasons for reduced risk of negative post‐acute outcomes may be related to differences in the viral spike protein or previous immunity from infection or vaccination, or both 6 . Importantly, as a non‐negligible number of children in our cohort developed Long Covid even when infected by Omicron and some children infected with pre‐omicron virus were still symptomatic at 18 months follow‐up, offering care to these families and studying this condition should remain a public health priority.…”
Section: Multivariate or (95% Ci) For 3 Months Follow‐up P Multivar...mentioning
confidence: 99%
“…Prior immunity to SARS-CoV-2 is unlikely to explain the lower risk because less than half the children were still infection-naïve in June/July 2021 ( 39 ), consistent with reports from other similar high income countries, and reinfection with Delta in previously-infected children was uncommon ( 40 ). Notably, mRNA vaccination has been shown to significantly reduce PIMS-TS risk in adolescents ( 41 ), most likely by preventing SARS-CoV-2 infection ( 42 ). In England, however, vaccination of adolescent children only began after September 2021, while vaccination of 5–11 year-olds only began after February 2022.…”
Section: Discussionmentioning
confidence: 99%